Polysiloxane-poly(propylene oxide) hybrid discs as solid phase in anti-HCV detection using a recombinant core protein - Taghavini, S. A. [UNESP]; Mikawa, A. Y. [UNESP]; Yamanaka, H. [UNESP]; Henrique-Silva, F.; Costa, P. I. (Elsevier B.V., 2008)
In this work, siloxane-poly(propylene oxide) discs (PPO disc) prepared using the sol-gel process were used as solid phase in enzyme-linked immunosorbent assays (ELISA) for the detection of anti-hepatitis C virus (HCV) antibodies. The HCV RNA from serum (genotype 1b) was submitted to the RT-PCR technique and subsequent amplification of the HCV core 408 pb. This fragment was cloned into expression vector pET42a and expressed in Escherichia coli as recombinant protein with glutathione S-transferase (GST). Cell cultures were grown and induced having a final concentration of 0.4 x 10(-3) mol L-1 of IPTG. After induction, the cells were harvested and the soluble fraction was analyzed using polyacrilamide gel 15% showing a band with an approximate molecular weight of 44 kDa, the expected size for this GST-fused recombinant protein. The recombinant protein was purified and continued by immunological detection using HCV-positive serum and showed no cross-reactivity with positive samples for other infectious diseases. An ELISA was established using 1.25 ng of recombinant protein per PPO disc, a dilution of 1: 10,000 and 1:40 for a peroxidase conjugate and serum, respectively, and solutions of hydrogen peroxide and 3,3',5,5'-tetra-methylbenzidine in a ratio of 1: 1. The proposed methodology was compared with the ELISA conventional polystyrene-plate procedure and the performance of the PPO discs as a matrix for immunodetection gave an easy synthesis, good performance and reproducibility for commercial application. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: hepatitis C virus; core protein; recombinant antigen; siloxane-poly(propylene oxide) discs